Relationship between Physical Activity and Age on Flatfoot in Children - Jasrin, Carmellia Janice; Mayasari, Wulan; Rakhmilla, Lulu Eva (Althea Medical Journal, 2016)
Background: Modern technology has decreased physical activities of most people, especially children. A low physical activity is one of the risk factors of flatfoot. Flatfoot is a flattening of medial longitudinal arch of the foot (MLA) affecting humanâs body posture and gait. The objective of this study was to analyze the relationship between physical activity and age on flatfoot.Methods: This study selected 271 children from the elementary school of Cikeruh 1, Jatiroke 1, and Paripurna using cluster random sampling method. Data were collected from August to November 2015. The primary data were collected using questionnaire to determine the physical activity level and footprint method to measure MLA height which was counted using Arch Index (AI). If the AI>0.26, it was considered low arch/flatfoot. Statically, the collected data were analyzed by Fisherâs exact test.Results: From a total of 271, 151 (55.7%) children had a low activity level with 120 of them (44.3%) were flatfoot, whereas in 113 (41.7%) children with an intermediate activity level, 76 children (28.0%) were flatfoot; and from a total of 7 (2.6%) children with a high activity level, 4 children (1.5%) were flatfoot. There was a negative correlation between age and arch index, right foot (r=-1.67;p=0.006), left foot (r=-1.56;p=0.01). This study proved that there was a relationship between the level of physical activity and flatfoot (Fisher=6.125/p=0.040).Conclusions: The Arch Index of the foot becomes smaller with age with an inverse correlation and low physical activities have been proved to have contibution to flatfoot occurrence. [AMJ.2016;3(3):396â400]Â DOI: 10.15850/amj.v3n3.887Â